Off-Label Uses of Topical Vitamin D in Dermatology: A Systematic Review. Issue 2 (March 2014) - Wat, Heidi; Dytoc, Marlene
Background: Topical vitamin D is approved by the US Food and Drug Administration for the treatment of psoriasis but is also used off-label in the treatment of a variety of cutaneous diseases despite a lack of evidence-based guidelines. Objective: The objective of this study was to provide evidence-based clinical guidelines for the off-label use of topical vitamin D in the treatment of dermatologic disease. Methods: A systematic literature review was conducted via the MEDLINE, Embase, and CENTRAL databases for off-label uses of topical vitamin D analogues in the treatment of dermatologic disease other than psoriasis. The data were synthesized, and evidence-based recommendations were rendered according to the highest level of evidence available. Results: A total of 165 articles met the inclusion criteria. A moderate to strong recommendation was given for the use of topical vitamin D in combination with corticosteroids and phototherapy in vitiligo and as monotherapy for various ichthyoses, morphea, pityriasis alba, prurigo nodularis, and polymorphous light eruption. There is evidence showing that topical vitamin D is ineffective in the treatment of actinic keratosis, seborrheic keratosis, lichen planus, seborrheic dermatitis, alopecia areata, chemotherapy-induced alopecia, and hypertrophic scars. Conclusion: Topical vitamin D analogues have an important role in the off-label treatment of dermatologic disease, but higher quality studies are still required.